Effect of Novel Nanocomposite Materials for Enhancing Performance of Thin Film Transistor TFT Model - Youssef Ahmed Mobarak; Moamen Atef (International Journal of Advances in Applied Sciences, 2016)
The potential impact of high permittivity gate dielectrics on thin film transistors short channel and circuit performance has been studied using highly accurate analytical models. In addition, the gate-to-channel capacitance and parasitic fringe capacitances have been extracted. The suggested model in this paper has been increased the surface potential and decreased the threshold voltage, whenever the conventional silicon dioxide gate dielectric is replaced by high-K gate dielectric novel nanocomposite PVP/La2O3Kox=25. Also, it has been investigated that a decrease in parasitic outer fringe capacitance and gate-to-channel capacitance, whenever the conventional silicon nitride is replaced by low-K gate sidewall spacer dielectric novel nanocomposite PTFE/SiO2Ksp=2.9. Finally, it has been demonstrated that using low-K gate sidewalls with high-K gate insulators can be decreased the gate fringing field and threshold voltage. In addition, fabrication of nanocomposites from polymers and nano-oxide particles found to have potential candidates for using it in a wide range of applications in low cost due to low process temperature of these nanocomposites materials.